Analysis of water property rights and responsibilities of rights holders in Tigum-Aganan Watershed, Philippines - Lizada, Joy C.; Alcala-Hall, Rosalie; Espinosa, Teresita S.; Rola, Agnes C. (2019)
The fragmentation of rights between water permit holders who exercise authority to access, exclude, and withdraw and other institutions with only shared responsibility over watershed management inhibits effective water-related decision making, resulting in conflicts that may lead to unsustainable water supply. This paper analyzes the nature and type of property rights that govern the surface water in the Philippines employing the property rights and responsibility nexus framework – using the Tigum-Aganan watershed (TAW) as a case. It explains the failure in addressing the sedimentation problem as a representation of the weak link among institutions which has adversely affected surface water supply. In addressing sustainability challenges, water property rights and the corresponding responsibilities should be clarified across the institutional hierarchy and coordinated among actors.
Keywords: Property rights; Watersheds; Watersheds - Management